The crucial role of blue light as a driver of litter photodegradation in terrestrial ecosystems - Wang, Qing-Wei; Pieristè, Marta; Kotilainen, Titta K.; Forey, Estelle; Chauvat, Matthieu; Kurokawa, Hiroko; Robson, T. Matthew; Jones, Alan G. (Springer Science and Business Media LLC, 2022)
Background and aim Wherever sunlight reaches litter, there is potential for photodegradation to contribute to decomposition. Although recent studies have weighed the contribution of short wavelength visible and ultraviolet (UV) radiation as drivers of photodegradation, the relative importance of each spectral region across biomes and plant communities remains uncertain. Methods We performed a systematic meta-analysis of studies that assessed photodegradation through spectrally selective attenuation of solar radiation, by synthesizing 30 published studies using field incubations of leaf litter from 110 plant species under ambient sunlight. Results Globally, the full spectrum of sunlight significantly increased litter mass loss by 15.3% ± 1% across all studies compared to darkness. Blue light alone was responsible for most of this increase in mass loss (13.8% ± 1%), whereas neither UV radiation nor its individual constituents UV-B and UV-A radiation had significant effects at the global scale, being only important in specific environments. These waveband-dependent effects were modulated by climate and ecosystem type. Among initial litter traits, carbon content, lignin content, lignin to nitrogen ratio and SLA positively correlated with the rate of photodegradation. Global coverage of biomes and spectral regions was uneven across the meta-analysis potentially biasing the results, but also indicating where research in lacking. Conclusions Across studies attenuating spectral regions of sunlight, our meta-analysis confirms that photodegradation is a significant driver of decomposition, but this effect is highly dependent on the spectral region considered. Blue light was the predominant driver of photodegradation across biomes rather than UV radiation.
Keywords: Biogeochemical cycling; Carbon fux; Decomposition; Litter traits; Spectral composition; Photodegradation; Meta-analysis